Anticipatory prediction in older readers. - Wong, Roslyn; Veldre, Aaron (Memory & Cognition, 2025)
It is well-established that skilled, young-adult readers rely on predictive processing during online language comprehension; however, fewer studies have investigated whether this extends to healthy, older adults (60 + years). The aim of the present research was to assess whether older readers make use of lexical prediction by investigating whether they demonstrate processing costs for incorrect predictions in a controlled experimental design. The eye movements of a sample of older adults (60–86 years) were recorded as they read strongly and weakly constraining sentences containing a predictable word or an unpredictable alternative that was either semantically related or unrelated. To determine whether predictive processing depends on the stimuli presentation format, a second experiment presented the same materials in a self-paced reading task in which each word of a sentence appears one at a time at the readers' own pace. Older adults showed processing benefits for expected input on eye-movement measures of reading. They also showed processing costs for unexpected input across both methodologies, but only when semantically unrelated to the best completion. Taken together, the results suggest that the use of predictive processes remains relatively preserved with age. The implications of these findings for understanding whether prediction is a fundamental component of online language comprehension are discussed.